A Study of Modern Technology in the Management of Hospitality Outfit (Global Journal of Management and Business Research, 2022)
Modern technology it come to spread everywhere it can be likened to a huge web, connecting all area by change. We may make significant changes in our process of doing business by using machines, but it is the change in every nature of what we do, brought about by the social change induced through the machines, that is the real meaning of technology to business. As a result of the far #x2013; reaching changes in the technology. We can no longer think or talk usefully of just a computer.